Complementary and Alternative Medicine for Idiopathic Parkinson’s Disease: An Evidence-Based Clinical Practice Guideline - Cho, Ki-Ho; Kim, Tae-Hun; Kwon, Seungwon; Jung, Woo-Sang; Moon, Sang-Kwan; Ko, Chang-Nam; Cho, Seung-Yeon; Jeon, Chan-Yong; Lee, Sang-Ho; Choi, Tae Young; Jun, Ji Hee; Choi, Jiae; et al. (Frontiers in Aging Neuroscience, 2018)
Patients with idiopathic Parkinson’s disease (IPD) require long-term care and are reported to use complementary and alternative medicine (CAM) interventions frequently. This CAM-specific clinical practice guideline (CPG) makes recommendations for the use of CAM, including herbal medicines, acupuncture, moxibustion, pharmaco-acupuncture, and qigong (with Tai chi) in patients with IPD. This guideline was developed using an evidence-based approach with randomized controlled trials currently available. Even though this CPG had some limitations, mainly originating from the bias inherent in the research on which it is based, it would be helpful when assessing the value of the CAM interventions frequently used in patients with IPD.